Toxic Risk Assessment in Emergency and Mental Health Services: A Multidisciplinary Study and Strategies for Application in Najran with a Comparison with Hospitals in Saudi Arabia - Hussain Dhafer Ali Dakhshan; Saeed Mohaamed S Alelyani; Ali Saeed Saad Alelyani; Mona Abdulaziz Ahmad Al salman; Ali Yahya Eissa Sabai; Ibrahim Saleh Mohammed Hashil; Mohammed Hussain M Alyami; Abdullah Mana Yousef Alsulaiman; Ali Mahdi Saleh Alyami; Ali Hashan Hamad Al Muhathil; Fahad Ahmed Qlil Alzahrani; Ali Saleh Hamad Al Muhathil; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Toxic risk assessment is a critical component of healthcare safety, particularly in emergency and mental health services where exposure to hazardous substances is a frequent concern. This study examines the implementation of toxic risk management practices across healthcare facilities in Najran, Saudi Arabia, focusing on strengths, challenges, and opportunities for improvement. Through a review of institutional protocols, staff training, and resource allocation, key findings reveal significant variability in preparedness levels among hospitals. Facilities like Prince Sultan Military Hospital demonstrate robust adherence to safety protocols, while others, such as Al-Khurma General Hospital, face challenges due to limited resources. The study highlights the success of Najran General Hospital in leveraging staff training programs, which serve as a model for enhancing safety in mental health services. However, issues such as inconsistent medication monitoring, insufficient technological support, and resource allocation gaps remain prevalent. Recommendations include enhancing staff training, developing standardized protocols, leveraging technology, and fostering collaboration among healthcare facilities. These strategies aim to improve toxic risk management practices, ensuring a safer healthcare environment for patients and staff. This research underscores the importance of tailored approaches that address institutional and regional challenges in toxic risk assessment.